2011
DOI: 10.1128/mbio.00011-11
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Signal Binding by the Pseudomonas aeruginosa Quorum-Sensing Signal Receptor LasR

Abstract: Many members of the LuxR family of acyl-homoserine lactone (acyl-HSL)-dependent quorum-sensing transcriptional activators are thought to have the unusual characteristics of requiring the signal ligand during polypeptide synthesis to fold into an active conformation and of binding signal extraordinarily tightly. This is the case for the N-3-oxo-dodecanoyl-HSL-dependent Pseudomonas aeruginosa virulence regulator LasR. We present evidence that LasR can fold into an active conformation in vivo in the absence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 26 publications
6
48
0
Order By: Relevance
“…Experimental evidence suggest that Vpu does not affect BST‐2 internalization, but rather prevents proper intracellular transportation of newly synthesized BST‐2 from the ER and TGN to the cell membrane 89, 90 (Fig. 2 #5) and/or from early endosomes to the cell surface 44, 88, 91 (Fig. 2 #6).…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence suggest that Vpu does not affect BST‐2 internalization, but rather prevents proper intracellular transportation of newly synthesized BST‐2 from the ER and TGN to the cell membrane 89, 90 (Fig. 2 #5) and/or from early endosomes to the cell surface 44, 88, 91 (Fig. 2 #6).…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%
“…2 #6). Vpu‐mediated inhibition of BST‐2 anterograde transport occurs in the absence of Ser52 and Ser56 phosphorylation 89, 90, 91.…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%
“…A typical LuxR-type protein is LasR from the opportunistic pathogen Pseudomonas aeruginosa . When its cognate signal AHL ( N -(3-oxo)-dodecanoyl L-homoserine lactone, OdDHL, Figure 1) is present at a quorate concentration, LasR binds this signal and is stabilized by it in an active, dimerized form that recognizes certain promoters and recruits transcriptional machinery to induce QS gene expression (Sappington et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In this experiment (Table 3) we used as positive control the DNA sequence of the lasI las box that is specifically bound by LasR/3O-C12-HSL (Schuster et al, 2004), and as negative control for LasR/3-O-C12-HSL binding and control of binding specificity we used the las box of rhlA that is only bound by RhlR in both the presence and absence of C4-HSL (in the first case it activates transcription, while in the second one it acts as a repressor: Medina et al, 2003b). It has been recently reported that some structural characteristics of LasR that affect its capacity to reversibly bind 3-O-C12-HSL, and ultimately to bind las boxes, are not maintained in the purified protein (Sappington et al, 2011). Thus it is preferable to use in vivo systems to determine LasR DNAbinding specificity rather than in vitro systems such as electrophoretic mobility shift assays.…”
Section: Lasr-binding Sequences Overlap Vbs1 and Vbs2mentioning
confidence: 99%